2020
DOI: 10.1149/1945-7111/abb7e8
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Selectivity of IrO2-Based Nano/Amorphous Hybrid Oxide-Coated Titanium Anodes in Acidic Aqueous Solutions: Oxygen Evolution and Lead Oxide Deposition

Abstract: The present study demonstrated that novel IrO2-Ta2O5/Ti anodes prepared by thermal decomposition at a low temperature of 380 °C have high reaction selectivity for oxygen evolution and metal oxide deposition in acidic aqueous solutions. Conventional IrO2-Ta2O5/Ti anodes are generally prepared at a temperature between 450 °C and 500 °C. However, if Pb(II) ions are present as an impurity in the electrolyte, the oxidation of Pb(II) ions occurs as an anodic side reaction, leading to deposition of PbO2 onto the conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
1
0
0
Order By: Relevance
“…of β-PbO 2 has also been reported as a by-product of electrolysis in a lead sulfate solution. 40 Effect of radiation wavelength.-We confirmed that PbO 2 particles were deposited in the upper part of the nanotubes with ∼3 μm length in both photoanodes. This could be explained by the short penetration depth of the incident light upon UV light irradiation.…”
Section: Resultssupporting
confidence: 53%
“…of β-PbO 2 has also been reported as a by-product of electrolysis in a lead sulfate solution. 40 Effect of radiation wavelength.-We confirmed that PbO 2 particles were deposited in the upper part of the nanotubes with ∼3 μm length in both photoanodes. This could be explained by the short penetration depth of the incident light upon UV light irradiation.…”
Section: Resultssupporting
confidence: 53%